Social Adjustment among in-School Adolescents with Learning Disabilities: Do Parental Socioeconomic Status and Peer Influence Play Any Role? - Temilade Silifatu Ayo; Kelechi Uchemadu Lazarus (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractSocial adjustment, a crucial aspect of everyone’s life, is needed to cope with one’s engagement with others in society and overall social life.  However, reports have shown that many in-school adolescents, particularly in Oyo State secondary schools, exhibit poor social adjustment. Therefore, this study investigated the predictive influence of parental socioeconomic status and peer influence on the social adjustment of in-school adolescents with learning disabilities. The study adopted the descriptive survey research design of the correlational type. The multistage sampling procedure was used. The three Senatorial Districts in Oyo State were enumerated. Twenty-seven public senior secondary schools (three from each local government area) were randomly selected. The Screening Inventory for Learning Disabilities was adopted to identify 452 in-school adolescents with learning disabilities. The instruments used were Peer Influence (r=0.76), Parental Socioeconomic Status (r=0.73), and Social Adjustment (r=0.92) scales. Data were analyzed using descriptive statistics and Pearson product moment correlation at the 0.05 level of significance. The findings showed that there was a significant relationship between peer influence and social adjustment (r=0.46) as well as between parental socioeconomic status and social adjustment (r=0.27) of in-school adolescents with learning disabilities. Based on the findings, the researchers made some recommendations for relevant stakeholders. However, the study calls for special educators and stakeholders to identify and support students with learning disabilities early, in order to enhance their social skills and long-term well-being.Keywords: adolescents’ social engagements, learning disabilities, peer influence, socio-economic status of parents.  AbstrakPenyesuaian sosial, aspek penting dari kehidupan setiap orang, diperlukan untuk mengatasi keterlibatan seseorang dengan orang lain dalam masyarakat dan kehidupan sosial secara keseluruhan. Namun, laporan telah menunjukkan bahwa banyak remaja di sekolah, khususnya di sekolah menengah Oyo State, menunjukkan penyesuaian sosial yang buruk. Oleh karena itu, penelitian ini menyelidiki pengaruh prediktif status sosial ekonomi orang tua dan pengaruh teman sebaya pada penyesuaian sosial remaja di sekolah dengan disabilitas belajar. Penelitian ini mengadopsi desain penelitian survei deskriptif dari jenis korelasional. Prosedur pengambilan sampel multitahap digunakan. Tiga Distrik Senatorial di Negara Bagian Oyo dihitung. Dua puluh tujuh sekolah menengah atas negeri (tiga dari setiap wilayah pemerintah daerah) dipilih secara acak. Inventaris Skrining untuk Disabilitas Belajar diadopsi untuk mengidentifikasi 452 remaja di sekolah dengan disabilitas belajar. Instrumen yang digunakan adalah skala Pengaruh Teman Sebaya (r=0,76), Status Sosial Ekonomi Orang Tua (r=0,73), dan Penyesuaian Sosial (r=0,92). Data dianalisis menggunakan statistik deskriptif dan korelasi momen produk Pearson pada tingkat signifikansi 0,05. Temuan penelitian menunjukkan adanya hubungan yang signifikan antara pengaruh teman sebaya dan penyesuaian sosial (r=0,46) serta antara status sosial ekonomi orang tua dan penyesuaian sosial (r=0,27) pada remaja di sekolah dengan disabilitas belajar. Berdasarkan temuan ini, para peneliti memberikan beberapa rekomendasi bagi para pemangku kepentingan terkait. Namun, studi ini menghimbau para pendidik khusus dan pemangku kepentingan untuk mengidentifikasi dan mendukung siswa dengan disabilitas belajar sejak dini guna meningkatkan keterampilan sosial dan kesejahteraan jangka panjang mereka.Kata kunci: keterlibatan sosial remaja, kesulitan belajar, pengaruh teman sebaya, status sosial ekonomi orang tua.